EFFECTIVENESS OF HEALTH EDUCATION ABOUT COMMUNITY – LED TOTAL SANITATION (CLTS) ON BEHAVIOR HAND WASHING WITH SOAP (HWWS) - Susana Nurtanti (Universitas Muhammadiyah Semarang, 2017)
Hand washing was the most important basic technique in the prevention and transmission of infections, 80% of common infectious diseases and 45% of serious infectious diseases. The habit of washing hands with soap was part of a healthy lifestyle that was one of the three pillars of health development, namely healthy living behavior, the creation of a healthy environment, and the provision of quality healthservices and affordable by all levels of society. The students surveys result of HWWS behavior in Gumiwang Lor village people proved that from total 525 families, 489 (93%) of them did not wash hands with soap. Many efforts had been done to increase the community awareness and behavior ofcommunity-led total sanitation (CLTS). This research was conducted to analyze the effectiveness of health education application on community-led total sanitation (CLTS) behavior of hand washing with soap (HWWS) on health cadres in Gumiwang Lor Village. The method was one group research with pre test- post test design. The sample of research was total sampling. The sample was health cadres in Gumiwang Lor Village which there were 23 people. The research instrument used questionnaire. Data was analyzed by t- test. The p-value of T paired was 0.000. The t-test showed there was a difference of HWWS behavior before and after the application of health education about CLTS. There was an increasing behavior in hand washing with soap (HWWS) after receiving health education on communityledtotal sanitation (CLTS). Keywords: Health Education, Community-Led Total Sanitation (CLTS), Handwashing With Soap (HWWS).